Strengthening Institutional Mechanisms for Human Rights Protection within Constitutional Principles (Jurnal Hukum Islam, 2026)
Human rights protection still faces challenges in ensuring the integration of constitutional principles and the effectiveness of institutional implementation during globalization and increasing complexity of modern state governance. This study analyzes the constitutional principles and institutional mechanisms of human rights protection in Ukraine and Indonesia, identifying their characteristics, similarities, and differences, and developing a model for strengthening institutions based on the rule of law that is integrated with international standards and responsive to contemporary challenges. This study uses a normative juridical method with a conceptual and comparative approach to analyze legal doctrine, regulations, and institutional practices in both countries. The research findings indicate that the rule of law is the main foundation of the human rights protection system, while justice, equality, and legality serve as operational principles in maintaining the balance of constitutional values, resolving legal conflicts, and addressing regulatory gaps. Legality is substantively interpreted not only as compliance with norms but also as an indicator of the effectiveness of state administration and a guarantee of legal certainty. This study confirms that the effectiveness of human rights protection requires systemic strengthening of institutions and regulatory architecture based on the rule of law. Therefore, it is necessary to strengthen institutions that integrate the principles of justice, equality, and legality in the design of regulations and state oversight mechanisms in order to bridge the normative and empirical gaps in the implementation of human rights protection.
Keywords: Constitutional principles; Human rights; Institutional strengthening; Legality; Rule of law